Potensi fungisida organik untuk pengendalian Ganoderma pada tanaman kelapa sawit [Potency of organic fungicide to controle Ganoderma sp. of oil palm] - Happy WIDIASTUTI; Deden Dewantara ERIS; Djoko SANTOSO (E-Journal Menara Perkebunan, 2016)
Ganoderma sp. is an important pathogen causes stem rot disease in the cultivation of oil palm. Control of Ganoderma sp. using formulas contain natural organic active ingredients being developed by Indonesian Research Institute for Biotechnology and Bioindustry. Organic fungicide in two formula i.e.   liquid  and  pasta was  applied for a  period  of 3 months by drenching the uncolonized tissue of stem. Five treatments tested were drenching applications of organic fungicide  1) per week in liquid formula, 2) every 2 weeks in liquid formula, 3) every 4 weeks in liquid formula, 4) every 4 weeks in paste formula, and 5) control. Each of the treatments was treated on the 25 palm trees. The performance of the plant and Ganoderma sp. were observed for five months and subsequential incubation continued for 2 months to analyzed the levels of N, P, K and Cu in the leaves and the oil content of the palm fruits while FFB production was observed from 7 up to 13 months after application. Results of the experiments showed that the application of organic fungicide increased the growth of palm roots and especially weekly application produced the best compared with other treatments. There was a tendency of opening of leaf spear and induce oil palm to form a female flowers, increased levels of N, P, and K particularly on the treatment of applications every two weeks. The production of fruit average (PFA) and weights bunches at 5 months after application seems to rise particularly in the application of organic fungicide every week. Palm fruit oil content based either on fresh or dry weight was higher in applications of organic fungicide every 2 weeks compared with other treatments.[Keywords: Ganoderma diseases management, application times, organic pesticides, mature plants]  AbstrakGanoderma sp. jamur penyebab penyakit busuk pangkal batang merupakan patogen utama pada tanaman kelapa sawit. Pengendalian Ganoderma sp. menggunakan formula berbahan aktif organik alami sedang dikembangkan Pusat Penelitian Bioteknologi dan Bioindustri Indonesia. Fungisida organik diberikan dalam jangka waktu 3 bulan  yang diaplikasi dengan cara terlebih dahulu mengikis batang sawit terserang hingga jaringan segar. Lima perlakuan yang diuji adalah aplikasi fungisida organik tiap  1) minggu dalam formula cair, 2) 2 minggu dalam formula cair, 3) 4 minggu dalam formula cair, 4) 4 minggu dalam formula pasta, dan 5) kontrol. Masing-masing perlakuan diaplikasi pada 25 pohon kelapa sawit. Keragaan tanaman dan Ganoderma sp. diamati selama lima bulan dan selanjutnya inkubasi dilanjutkan selama 2 bulan untuk analisis kadar hara N, P, K dan Cu daun dan kadar minyak buah sawit, sedangkan produksi TBS diamati dari 7 hingga 13 bulan setelah aplikasi. Hasil percobaan menunjukkan bahwa pemberian fungisida organik tiap minggu menghasilkan perakaran yang paling banyak dibandingkan dengan perlakuan lainnya.  Terdapat kecenderungan terjadi pembukaan daun tombak dan peningkatan jumlah pohon yang membentuk bunga betina, peningkatan kadar hara N, P, dan K khususnya pada perlakuan aplikasi fungisida organik tiap dua minggu. Rata rata  bobot  tandan  (RBT)  dan bobot tandan  pada 5 bulan setelah aplikasi nampak meningkat khususnya pada perlakuan aplikasi fungisida organik tiap minggu. Kadar minyak buah sawit baik berdasarkan  bobot basah maupun kering lebih tinggi pada perlakuan aplikasi fungisida organik tiap 2 minggu dibandingkan dengan perlakuan lainnya.  [Kata kunci: pengendalian Ganoderma, frekuensi aplikasi, fungisida organik, tanaman sawit menghasilkan]